Development of the Inactivated QazCovid-in Vaccine: Protective Efficacy of the Vaccine in Syrian Hamsters - Zhugunissov, Kuandyk; Zakarya, Kunsulu; Khairullin, Berik; Orynbayev, Mukhit; Abduraimov, Yergali; Kassenov, Markhabat; Sultankulova, Kulyaisan; Kerimbayev, Aslan; Nurabayev, Sergazy; Myrzakhmetova, Balzhan; Nakhanov, Aziz; Nurpeisova, Ainur; et al. (Frontiers in Microbiology, 2021)
In March 2020, the first cases of human coronavirus infection COVID-19 were registered in Kazakhstan. We isolated the SARS-CoV-2 virus from the clinical material from the patients. Subsequently, a whole virion inactivated candidate vaccine, QazCovid-in, was developed based on this virus. To obtain the vaccine, a virus grown in Vero cell culture was used, which was inactivated with formaldehyde, purified, concentrated, sterilized by filtration, and then sorbed on aluminum hydroxide gel particles. The formula virus and adjuvant in buffer saline solution was used as a vaccine. The safety and protective effectiveness of the developed vaccine was studied on Syrian hamsters. The results of the studies showed the absolute safety of the candidate vaccine on the Syrian hamsters. When studying the protective effectiveness, the developed vaccine with an immunizing dose of 5µg/dose of a specific antigen protected animals from wild virus at a dose of 104.5 TCID50/ml. The candidate vaccine formed virus-neutralizing antibodies in vaccinated hamsters in titers from 3.3 ± 1.45 log2 to 7.25 ± 0.78 log2, which were retained for 6 months (observation period) in the indicated titers. The candidate vaccine suppressed the replication of the wild virus in the body of vaccinated hamsters, protected against the development of acute pneumonia and ensured 100% survival of the animals. At the same time, no replicative virus was isolated from the lungs of vaccinated animals. At the same time, a virulent virus was isolated from the lungs of unvaccinated animals in relatively high titers, reaching 4.5 ± 0.7 lg TCID50/ml. After challenge infection, 100% of unvaccinated hamsters became ill with clinical signs (stress state, passivity, tousled coat, decreased body temperature and body weight, and the development of acute pneumonia), of which 25 ± 5% were fatal. The findings paved the way for testing the candidate vaccine in humans in clinical trials.